Community Service in Improving Science Learning through the Development and Implementation of Canva Interactive Digital Teaching Materials at MI Terpadu Berkah Palangka Raya - Isnaeni Maulidiati Rahmah; Siska Sari; Tiara; Muhammad Syabrina; Istiyati Mahmudah; Zaitun Qamariah (Publikasi Inspirasi Indonesia, 2025)
The limited use of interactive teaching materials and learning technologies in the science subject at MI Terpadu Berkah Palangka Raya has led to low student motivation and suboptimal learning outcomes, primarily due to the reliance on conventional methods and printed worksheets. This community service activity aims to address these challenges by developing and assisting in the use of interactive digital teaching materials based on Canva. The implementation method starts with needs mapping, mentoring on creating digital books, and finally implementing and evaluating the use of the media in grade IV classrooms. The results showed a significant improvement in student motivation and understanding of science materials, as indicated by an average field test score of 85.29% (very feasible category). Additionally, teachers provided positive feedback with an evaluation score of 72.05%. The activity positively impacted the digital learning process at MI Terpadu Berkah Palangka Raya and enhanced teachers’ capacity to develop independent technology-based teaching media.